2005
DOI: 10.1103/physrevlett.95.075502
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of theαεTransition in Shock-Compressed Iron via Nanosecond X-Ray Diffraction

Abstract: In situ x-ray diffraction studies of iron under shock conditions confirm unambiguously a phase change from the bcc (alpha) to hcp (epsilon) structure. Previous identification of this transition in shock-loaded iron has been inferred from the correlation between shock-wave-profile analyses and static high-pressure x-ray measurements. This correlation is intrinsically limited because dynamic loading can markedly affect the structural modifications of solids. The in situ measurements are consistent with a uniaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(123 citation statements)
references
References 16 publications
7
111
1
4
Order By: Relevance
“…It would be interesting to see whether experimental efforts could confirm the newly predicted shock-induced β-stacking fault structure, similar to studies performed on the shock-induced phase transformations in iron. 13,14 Since the β-stacking fault structure has been found to be energetically competitive-both by the classical MEAM potential and electronic structure calculations-this might be another metastable phase that can occur during nonequilibrium conditions. Furthermore, theoretical and experimental investigation on polycrystalline Ga-similar to studies performed for iron 44 -would shed further light on the fascinating topic of shock-induced phase transformations in polymorphic materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to see whether experimental efforts could confirm the newly predicted shock-induced β-stacking fault structure, similar to studies performed on the shock-induced phase transformations in iron. 13,14 Since the β-stacking fault structure has been found to be energetically competitive-both by the classical MEAM potential and electronic structure calculations-this might be another metastable phase that can occur during nonequilibrium conditions. Furthermore, theoretical and experimental investigation on polycrystalline Ga-similar to studies performed for iron 44 -would shed further light on the fascinating topic of shock-induced phase transformations in polymorphic materials.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Prompted by these latter simulation studies, in situ x-ray diffraction experiments subsequently confirmed the NEMD predictions for Fe single crystals compressed in the [100] crystallographic direction. [13][14][15] More recently, NEMD simulations have been used to investigate atomic-scale plastic deformation processes in more complex crystal structures beyond these relatively simple fcc, hcp, and bcc lattices. For instance, the mechanical (i.e., nonreactive) shock response of the high-explosive crystals HMX 16 and RDX 17 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A lthough the shock compression of condensed matter has been a field of study for many decades [1][2][3][4][5][6] , our understanding of what occurs at the lattice level during the passage of a shock through a condensed matter system is woefully incomplete. It is well known that many simple metals, when shocked to high stresses under the constraint of uniaxial macroscopic strain, exhibit a peak stress-volume relationship (the 'PV Hugoniot') that closely follows the pressure-volume curve for hydrostatic compression.…”
mentioning
confidence: 99%
“…The crystallographic nature of the phase was not determined until later with static compression measurements using x-ray diffraction by Jamison and Lawson [22]. It was not until recent in-situ x-ray diffraction experiments of laser shocked samples that this was confirmed [23]. With the recent success of in-situ x-ray diffraction in determining the crystal structure of shocked iron, we will use iron as the example to discuss the x-ray diffraction technique for isentropically compressed samples.…”
Section: Diffraction From Iron [100] Crystalsmentioning
confidence: 96%